Hubungan Indeks Massa Tubuh Dengan Kejadian Hipertensi Pada Lansia di Puskesmas Sei Langkai kota Batam Tahun 2021 - Revi Yulia; Dedi Siska, Dino Himawan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2021)
This study aims to determine the relationship between body mass index and the incidence of hypertension in the elderly at the Sei Langkai Health Center, Batam city in 2021. The design of this study used an analytical observational research design with a cross sectional. Respondents in this study 64 respondents. The sampling technique used is purposive sampling. The results of the chi-square test show p value = 0.000 (< 0.05) so Ho is rejected, this indicates a relationship between Body Mass Index and Hypertension Incidence in the Elderly at the Sei Langkai Health Center Batam City in 2021. The conclusion of this study is the elderly who have weight overweight is at risk for hypertension. It is recommended to health care workers to be able to provide health education about the importance of maintaining an ideal body weight to the elderly